Hasil Pengamatan Diagnosa Klinik Terhadap Diagnosa Patologi pada Penderita Radang Usus Buntu - Prawito, Prawito (Universitas Gadjah Mada, 1980)
The purpose of this paper is to review 309 patients of appendicitis operated in the Department of Surgery, Gadjah Mada University Hospital, Yogyakarta, between 1972 - 1976. Among the pa. tients 81 are males and 228 are females. The peak incidence of appendicitis is between 15 - 20 years of age. Results of the clinical diagnosis compared with the pathological diagnosis are as follows;81,8% is chronic appendicitis; 44,4% is acute appendicitis; 64,4% is chronic appendicitis with acute exacerbation; 60% is periappendicular infiltrate and 1,9% is normal appendix.Fecaliths within the lumen-of the appendix are found in 136 patients (44%); eggs of elscaris in 8 patiens (2,6%).Key Words: appendicitis - periappendicular infiltrate - Ascaris - normal appendix - fccaliih